RISIKO DAN KENDALA DALAM MENJALANKAN STRATEGI PENGEMBANGAN BANK SYARIAH - Siti Aisyah Nuraini; Mulya Jayanti Putri; Heni Noviarita (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2026)
The development strategy of Islamic banks is highly influenced by the institution’s ability to manage both internal and external risks, as well as to overcome structural, regulatory, and cultural constraints that remain systemic barriers within the Islamic financial ecosystem. Internal risks include limited liquidity instruments, risks associated with profit-and-loss sharing financing, and low human resource competence. Meanwhile, external risks arise from national economic policies that are still interest-based and from global economic fluctuations that affect asset stability.This study employs a qualitative approach using the literature review method, in which data are collected from books, national and international journals, and relevant regulations. The analysis is conducted descriptively and critically through theoretical synthesis and interpretation of previous research findings related to risks and challenges in the development of Islamic banks.The findings reveal that the implementation constraints in Islamic banking development require a strategic and integrative approach through strengthening risk management, diversifying products and digitalizing services, improving Islamic financial literacy, and ensuring stronger government policy support for an inclusive Islamic financial ecosystem. These findings are expected to serve as a foundation for formulating policies and strategies to enhance competitiveness and ensure the sustainability of Islamic banking in Indonesia.